DINAMIKA KOMITMEN GURU PROFESIONAL DALAM MENYEIMBANGKAN BEBAN ADMINISTRATIF DAN PERUBAHAN KARAKTERISTIK SISWA DALAM MENYIKAPI KEBIJAKAN EFISIENSI - Imam Syafii; Hanif Abdul Rahman; Kalimatussa’diyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Increasing administrative burdens often hinder teachers' teaching effectiveness, while technological developments and social changes also influence student characteristics. This research aims to analyze how teachers balance their professional commitments in dealing with administrative demands and adapt teaching methods according to changes in student character in the digital era. This research uses a qualitative approach with a literature study method, examining various relevant academic sources. The research results show that administrative burden has the potential to reduce teacher focus in the learning process. However, strategies such as the use of technology, effective time management, and institutional support can help teachers maintain their professionalism. These findings provide insight for policy makers and educational institutions in establishing policies that support a balance between administrative and teaching tasks in order to maintain the quality of education.